The Illustrations Emotional Coloring Influence in Advertising Messages on Attitudes Toward a Fiction Book and the Advertising Message - Hubin, Kyryl (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2026)
The relevance of the study is determined by visual components growing role in advertising communication and the insufficient representation of experimental studies examining the advertising illustrations psycohological influence specifically in the book advertising field. In contemporary media environments, illustrations not only attract attention but also shape emotional expectations, influence a product perception, and affect attitudes toward advertising messages. Despite extensive research in advertising psychology and media psychology, the emotionally colored illustrations impact on attitudes toward fiction books remains insufficiently explored. The aim of the study was to investigate positively and negatively emotionally colored illustrations influence in advertising messages on attitudes toward a fiction book and the advertising message itself. The study employed the subjective scaling methods and polar profiles (semantic differential). Statistical data analysis included one-way analysis of variance (ANOVA), Tukey post hoc comparisons, and effect size calculations using Cohen’s d, η2, and ω2 coefficients. The sample consisted of 50 first-year university students aged 16–20, divided into one control group and two experimental groups. The stimulus materials included a fantasy book annotation and two variants of illustrations with different emotional valence: a positively colored illustration (“kind”) and a negatively colored illustration (“harsh”). The control group evaluated the annotation without illustrations. The results demonstrated that emotionally colored illustrations significantly influenced respondents’ perceptions of both the book and the advertising message. Negatively emotionally colored illustrations reduced the characters subjective perception as interesting and contributed to perceiving the psychological book atmosphere as less comfortable. At the same time, positively emotionally colored illustrations unexpectedly reduced originality evaluations of both the book and the advertising message, a plot introduction engaging nature, and the correspondence of the advertisement to readers’ interests and expectations. Significant differences between groups were identified for several subjective scaling indicators and one pair of polar profile characteristics. Large effect sizes were observed for a number of statistically significant differences. The findings suggest that the emotional coloring of illustrations may function as an emotional frame influencing the interpretation of textual information. Excessively harmonious and positively colored visual images do not necessarily strengthen positive attitudes toward a fiction book, especially when the annotation contains dramatic, conflict-related, or threatening plot elements. The study expands current understanding of advertising perception psychological mechanism in book marketing field and highlights the importance of emotional congruence between visual elements and the semantic atmosphere of a literary work.